Identifying Teaching at the Right Level (TaRL) Approach Practices in Primary School Learning - Sefriyana Sefriyana; Herlina Herlina; Asriani Asriani; Rizal Rizal; Ryan A. Pratama (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to identify the implementation of the Teaching at the Right Level (TaRL) approach in sixth-grade learning at SD Negeri Model Terpadu Madani. Using a descriptive qualitative method, data were collected through in-depth interviews, classroom observations, and document analysis. The results indicate that TaRL is implemented through three key stages: initial diagnostic assessment to map student ability levels, grouping based on literacy and numeracy levels, and level-based differentiated instruction accompanied by ongoing formative evaluation. Triangulated data from multiple sources strengthens the finding that this approach enhances learning relevance and accommodates student diversity. The main challenges include increased teacher workload, time constraints, and the need for ongoing institutional support and professional training. This research contributes to the development of level-based instructional strategies in Indonesian primary education and recommends the systemic integration of the TaRL approach into teacher training programs and the Merdeka curriculum framework